(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the key challenges faced in English lexicography, the field responsible for the creation and maintenance of dictionaries. It identifies six major problem areas: the expansive scope of the English language, representation of regional and dialectal variations, semantic complexity, cultural biases, technological adaptation, and ethical concerns. The discussion emphasizes the tension between documenting the language as it evolves and meeting the practical needs of users. By highlighting the dynamic and multifaceted nature of lexicography, the article underscores its importance as both a linguistic and cultural endeavor. It concludes by calling for continued innovation and inclusivity to address these challenges and ensure the relevance of dictionaries in a rapidly changing world.